Concept And Potential For The Implementation Of Smart Parking System In Indonesia: A Literature Review - Joisce; Hanum Putri Kamelianti; Rizal Aprianto (Universitas Islam Kuantan Singingi, 2025)
The rapid development and growth of the Internet of Things (IoT) has improved the quality of life and strengthened various areas of society. Many cities around the world are looking forward to becoming smart. One of the most popular use cases in smart cities is the implementation of smart parking solutions, as it allows people to optimize time, reduce fuel consumption, and carbon dioxide emissions. Smart parking solutions have a defined architecture with specific components (sensors, communication protocols, and software solutions). Although there are only three components that make up a smart parking solution, it is important to mention that each component has many types that can be used in the implementation of this solution. This article identifies the most frequently used types of each component and highlights the usage trends in the established analysis period. This provides a complementary perspective and is a very useful source of information. society can use this information to decide on the selection of the type of component to be used. implementing smart parking solutions. For this purpose, here we review some of the works related to the implementation of smart parking solutions. To achieve this goal, a semi-cyclical adaptation of the Research Methodology action combined with a systematic review was used to select articles related to the research subject. The most relevant of the types of components that should be considered when implementing smart parking solutions. The implementation of smart parking in Indonesia promises many benefits, especially in increasing efficiency and transparency. However, challenges such as high costs, infrastructure readiness, and technological literacy must be overcome so that this system can run optimally and inclusively.